دابہ الارض کا مفہوم اور خروج: قرآن و سنت کی روشنی میں ایک مطالعہ: Conception and Appearance of Dābatul Arz: A Study in the Light of Quran and Sunnah (Al-Qamar, 2025)
This Paper discusses “Dābbatul Arz” in the light of Quran and Sunnah. The word Dābbah is used nine times in Holy Quran. The literal meaning of word “Dabbah’ is moving. According to Surah Numal verse NO. 82, “And when the time for the fulfillment of our world against them will come, we shall bring forth for them a beast from the Earth who will speak to them because people did not believe in Our Signs”. The real discussion is that whether Dābbah is a beast or man. Majority of Scholars believe that it is a beast, However, there are strong evidences that it is a man.
Keywords: Dābbatul Arz, conception, appearance, Quran, Sunnah